Palpable purpura with foot drop: Common presentations in an uncommon disease - Teena Ramesh Mathanda; Ramesh Bhat; Jayaprakash Alva (Wolters Kluwer Medknow Publications, 2015)
Churg-Strauss syndrome is a rare disease manifested by hypereosinophilia, vasculitis and tissue infiltration. This report describes the case of a 45-year-old man who presented with a history of fever, difficulty in breathing, reddish lesions over the extremities and inability to walk since two weeks. The cutaneous features prompted us to conduct serial lab investigations which led to an early, potentially life saving diagnosis.